2021
DOI: 10.1080/13696998.2021.1960714
|View full text |Cite
|
Sign up to set email alerts
|

Payer budget impact of an artificial intelligence in vitro diagnostic to modify diabetic kidney disease progression

Abstract: To evaluate the U.S. payer budget-impact of KidneyIntelX, an artificial intelligence-enabled in vitro diagnostic to predict kidney function decline in Type 2 Diabetic Kidney Disease (T2DKD) patients, stages 1-3b. Materials and MethodsWe developed an Excel-based model according to International Society of Pharmacoeconomics and Outcomes Research (ISPOR) good practices to assess U.S. payer budget impact associated with use of the KidneyIntelX test to optimize therapy T2DKD patients compared to standard of care (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Inclusion of time‐to‐event outcomes ensures that clinicians are provided with performance information to support the interpretation of test results. We performed additional analyses on KidneyIntelX which have demonstrated that cost savings are derived from deployment of KidneyIntelX testing for a large population of patients with DKD, compared to the standard of care 24 …”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of time‐to‐event outcomes ensures that clinicians are provided with performance information to support the interpretation of test results. We performed additional analyses on KidneyIntelX which have demonstrated that cost savings are derived from deployment of KidneyIntelX testing for a large population of patients with DKD, compared to the standard of care 24 …”
Section: Discussionmentioning
confidence: 99%
“…Third, an economic analysis of these models may be overly optimistic because it suggests delay or prevention of 5000 dialysis starts in a hypothetical cohort of 100,000 patients. Given the internal validation cohort has a kidney failure rate of 5% over 5 years, this would suggest that simply providing a risk score from a modestly accurate model would affect every dialysis start (9,10).…”
Section: Artificial Intelligence As a Solutionmentioning
confidence: 99%
“…Machine learning-based predictive models have demonstrated their ability to outperform risk calculators developed using conventional statistical methods for cardiovascular disease events and comorbidities such as diabetes and hypertension (10), demonstrating their potential to improve risk prediction and aid medical decision-making. If early detection of patients with a higher risk of CKD is desired, previous evidence on the implementation of machine learning algorithms to stratify risk of CKD suggests that this could be more efficient and cost-effective than traditional population-based screening methods (9,11,12). Furthermore, risk stratification could be associated with a significant decrease in the number of individuals who required closer monitoring of the glomerular filtration rate (eGFR) and an increase in the proportion of patients for whom a treatment change is indicated.…”
Section: Risk Stratification Using Ai For Ckd Managementmentioning
confidence: 99%
“…For example, a study estimated the budgetary impact in the United States of implementing an AI-based risk stratification system for patients with type 2 diabetic kidney disease (stages 1–3b). The overall result is that the undiscounted savings in the 5-year base case for 100,000 patients tested with the system were $1.052 billion, mainly attributed to slowing disease progression ( 9 ).…”
Section: Ai and Health Carementioning
confidence: 99%
See 1 more Smart Citation